The moroccan banking system and FinTech deployment: an overview of the literature - Luca Federico Battanta; Giuliano Lancioni; Manuela Giolfo; Francesca Magli (European Journal of Islamic Finance)
This study provides an in-depth analysis of the Moroccan financial system by examining key banking institutions, their characteristics, and their services. Under King Mohammed VI’s leadership, Morocco has emerged as one of the most financially advanced Mediterranean countries and the most developed in the Maghreb. Its openness in tourism and finance has facilitated the growth of both conventional and Islamic banking sectors. Using a qualitative methodology, this research follows a structured approach. First, a literature review examines academic and regulatory perspectives on Morocco’s financial system. Then, we analyze Moroccan banks by classifying them as commercial or business institutions and distinguishing between local and foreign financial entities. The study categorizes services into retail, corporate, and digital (FinTech), focusing on Sharia-compliant banking and its customer offerings. Furthermore, it assesses the evolution of digital financial services among Moroccan banking groups and foreign-owned banks. A unique aspect of this research, coauthored by management scholars and Arab studies experts, is its examination of how Moroccan banks communicate with customers, including language use and segmentation based on Sharia compliance. The findings will highlight Morocco’s banking strengths and potential improvements that could inspire financial strategies in Italy and other European countries with significant Muslim communities. Additionally, this study identifies best practices for expanding Sharia-compliant services to the hundreds of thousands of Muslim immigrants from Morocco and the broader Maghreb region.